The Relation of TMPRSS2 Gene Polymorphism to COVID-19 Severity of Indonesian Population in Jakarta - Erlin Listiyaningsih; Rizkyana Avissa; Shinta Dewi Permata Sari; Wening Tri Mawanti; Dewi Martalena (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: The COVID-19 disease caused by the SARS-CoV-2 virus has diverse symptoms, ranging from asymptomatic, mild symptoms such as flu-like illness and pneumonia to acute respiratory distress syndrome, which ends in death. Until now, the mechanism of the COVID-19 disease that causes widespread symptoms and the severity and factors that influence it are still unclear. During viral internalization, it needs to be cleaved by the serine protease encoded by the TMPRSS2 gene. It is hypothesized that higher expression of the TMPRSS2 gene causes higher virus internalization into cells, leading to more severe symptoms in patients. Methods: The Single Nucleotide Polymorphism Genotype Test was carried out to prove whether the TMPRSS2 gene affects the severity of COVID-19, as evidenced in other viral respiratory diseases. With a better understanding of gene expression related to this disease, it is hoped that we can better understand the mechanism of COVID-19 and establish better therapies and prevention against it. In this study, 68 COVID-19 patients participated and were categorized into two groups based on their clinical symptoms, namely mild symptoms without symptoms (n=12) and Moderate-Severe symptoms (n=56). PBMC cells were isolated from the patient. Then the DNA was extracted and used as a template in the SNP Genotyping of the TMPRSS2 rs2070788 gene variant. Results: The results showed that 35 samples had A/A homozygous genotypes, 29 A/G heterozygous samples, and 4 G/G homozygous samples. n=29) and heterozygous A/G (n=23), whereas only 4 were homozygous G/G. In addition, the homozygous G/G genotype was only detected in the moderate-severe group. Conclusions: A more significant number of samples from the asymptomatic mild symptom group is needed to statistically prove that homozygous G/G variants or G alleles are generally associated with the severity of COVID-19 patients.